Operation strategy of battery energy storage systems for stability improvement of the Korean power system. (15th December 2022) - Aryani, Dwi Riana; Song, Hwachang; Cho, Yoon-Sung
Abstract: In accordance with the energy transition roadmap of the Korean government, the Korean power system needs to significantly increase the use of renewable energy sources (RES) in the future. This may cause an amount of increase in converter-interfaced generators (CIG) for integrating RES to the utility grid substituting the conventional synchronous generators, and one can easily expect that a critical decrease in the system inertia will occur in the future power system, leading to some stability issues related to that. Besides, considering the short-term state of the Korean power system, another stability issue may arise due to the delayed reinforcement of the shared network connecting large-scaled generation plants. Several countermeasures such as generator tripping and generation curtailment are proposed to overcome stability issues. A combined action with generator tripping and generation curtailment is applied to stabilize the system after the critical event, however generation curtailment might reduce the economical operation of the system. Using their fast response characteristic, battery energy storage systems (BESS) are regarded as a countermeasure to relieve the curtailment. After adequate transmission network reinforcement for the large power plants is made, their long-term application needs to be examined, which is to maintain the frequency stability for the system in low-inertia situations. This study aims to design the BESS control strategy for improving stability as well as to determine key control parameters of the BESS. The proposed control strategy of BESS for stability enhancement is proven to be effective in overcoming stability issues in the short-term and long-term operation of the Korean power system. Highlights: BESS can be used to relieve the generation curtailment for power system stability. Transient droop parameter has a key role in GCR-BESS to provide fast power support. Adding FR application with proper settings can improve the GCR-BESS effectiveness. The GCR-BESS also enhances frequency stability in a low inertia power system.